Direct visualization of a strain-induced dynamic stress network in a SEBS thermoplastic elastomer with in situ AFM nanomechanics. (3rd June 2020) - Liu, Haonan; Liang, Xiaobin; Nakajima, Ken
Abstract: Thermoplastic elastomers (TPEs) may generate a residual strain after being stretched, which hinders their potential for use in high-performance materials. However, the mechanism of the residual strain formation has not been sufficiently elucidated thus far. Here, we used atomic force microscopy-based nanomechanical mapping to investigate a stretched TPE specimen consisting of poly(styrene- b -ethylene- co -butylene- b -styrene) with a content of 15 wt% styrene (SEBS-15). In the SEBS-15 polymer structure that maintained a strain of 0.5, hard-segmental (HS) amorphous domains aggregated by poly(styrene) segments deformed and became oriented parallel to the stretching direction, whereas soft-segmental rubbery domains aggregated by poly(ethylene- co -butylene) segments elongated, formed a stress network using the HS domains as junction points. Moreover, an in situ observation adopted for the stretched SEBS-15 revealed that HS domains therein underwent a relative displacement and partial separation that was influenced by the formed stress network, which was strongly related to the irreversible phenomena.